Genetic diversity of Diaphorina citri (Hemiptera: Liviidae) unravels phylogeographic structure and invasion history of eastern African populations. Issue 7 (17th July 2022) - Ajene, Inusa Jacob; Khamis, Fathiya Mbarak; van Asch, Barbara; Pietersen, Gerhard; Seid, Nurhussen; Wairimu, Anne Wambui; Ombura, Fidelis Levi; Akutse, Komivi Senyo; Sétamou, Mamoudou; Subramanian, Sevgan; Mohammed, Samira; Ekesi, Sunday
Abstract: The Asian citrus psyllid ( Diaphorina citri Kuwayama) is a key pest of Citrus sp. worldwide, as it acts as a vector for Candidatus Liberibacter asiaticus, the bacterial pathogen that causes citrus Huanglongbing. Diaphorina citri has been reported in Kenya, Tanzania, and more recently in Ethiopia. This study assessed the genetic diversity and phylogeographic structure of the pest to gain insights into the potential sources of its introduction into Africa. Population structure and differentiation of D. citri populations from China, Ethiopia, Kenya, Tanzania, and the USA were assessed using 10 microsatellite loci. Additionally, five new complete mitogenomes of D. citri collected in China, Ethiopia, Kenya, Tanzania, and the USA were analyzed in the context of publicly available sequences. Genotype data grouped the D. citri populations from Kenya and Tanzania in one cluster, and those from Ethiopia formed a separate cluster. The two genetic clusters inferred from genotype data were congruent with mitochondrial sequence data. The mitogenomes from Kenya/Tanzania/China had 99.0% similarity, and the Ethiopia/USA had 99.9% similarity. In conclusion, D. citri populations in eastern Africa have different sources, as the Kenyan and Tanzanian populations probably originated from southeastern Asia, while the Ethiopian population most probably originated from the Americas. Abstract : The Asian citrus psyllid (Diaphorina citri Kuwayama) is a key pest of Citrus sp. worldwide, as it acts as a vector for Candidatus Liberibacter asiaticus, the bacterial pathogen which causes citrus Huanglongbing. This study assessed the genetic diversity and phylogeographic structure of the pest to gain insights into the potential sources of its introduction into Africa. The research showed, D. citri populations in eastern Africa have different sources, as the Kenyan and Tanzanian populations probably originated from China while the Ethiopian population most probably originated from the USA.